FORMULASI STRATEGI PENATAAN PEDAGANG KAKI LIMA DI KABUPATEN JOMBANG MENGGUNAKAN MATRIK QUANTITATIVE STRATEGIC PLANNING (QSP) (FORMULATION STRATEGY OF STREET VENDORS IN JOMBANG REGENCY USING QUANTITATIVE STRATEGIC PLANNING MATRIX) - Kristian Budi T (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
Everyone has the right to have a decent living, including street vendors. Street vendor, as an informal livelihood profession, is currently exist as two sides of a coin. Often their existence is considered threatening the beauty of urban faces so it needs to be addressed and sterilized. The emergence of a variety of urban problems such as congestion and slum are often identified with the existence of their activities. On the other hand, their existence can be considered a positive side to form a more vibrant urban face, if it can be handled properly, and can be an alternative provider of goods that are cheaper. This study is to formulate the appropriate strategies that can be implemented by the Government of Jombang regency as a regulator in creating harmony and integrity among the elements of society in the region. The result of this research is structuring street vendors that can be done by carrying out supervision function to public space. The form of supervision can be by periodical updating of traders so that the number of street vendors can be controlled annually. The recommendation of this research is the implementation of strict regulations accompanied by the forms of appreciation and sanction to those who violate, the addition of security personnel and cleaning personnel, need to consider the aspects of harmony and harmony of buildings, and the need for synergy between agencies for the success of supervision and coaching programs Street vendors. Keywords: QSP Matrix, Street Vendor, Public Space, Informal Trading